2007
DOI: 10.1002/eji.200636800
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic CpG oligodeoxynucleotides augment BAFF‐ and APRIL‐mediated immunoglobulin secretion

Abstract: The B lymphocyte-activating factor belonging to TNF superfamily (BAFF) acts on B lymphocytes through BAFF receptor (BAFF-R), the transmembrane activator, calcium modulator, and cyclophilin ligand interactor (TACI), and the B cell maturation antigen (BCMA). Another cytokine, a proliferation-inducing ligand (APRIL), only binds to TACI and BCMA. In this study, we sought to determine the effect of Toll-like receptor agonists (TLR-A) on the expression of BAFF/APRIL receptors by murine splenic B lymphocytes. CpG oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 40 publications
10
113
1
3
Order By: Relevance
“…BAFF-or APRIL-stimulated cells yielded a significant increase in culture supernatant IgM, IgA, IgG1, IgG2a, IgG2b, and IgG3 compared with B lymphocytes that had been incubated with medium. Similar to our previous report (27) CpG ODN pretreatment of adult B lymphocytes also led to an increase in Ig production after BAFF and APRIL stimulation (Fig. 7A).…”
Section: Cpg Odn Renders Newborn B Lymphocytes Responsive To Baff Andsupporting
confidence: 92%
See 3 more Smart Citations
“…BAFF-or APRIL-stimulated cells yielded a significant increase in culture supernatant IgM, IgA, IgG1, IgG2a, IgG2b, and IgG3 compared with B lymphocytes that had been incubated with medium. Similar to our previous report (27) CpG ODN pretreatment of adult B lymphocytes also led to an increase in Ig production after BAFF and APRIL stimulation (Fig. 7A).…”
Section: Cpg Odn Renders Newborn B Lymphocytes Responsive To Baff Andsupporting
confidence: 92%
“…We (27) and others (19) have previously shown that adult TACI KO mice do not secrete IgG and IgA when stimulated with BAFF or APRIL. We therefore sought to understand whether decreased TACI expression in newborns would also lead to impaired Ig secretion.…”
Section: Newborn B Lymphocytes Do Not Secrete Igs In Response To Baffmentioning
confidence: 83%
See 2 more Smart Citations
“…This finding was also confirmed by the nearly homogeneous genetic background of worldwide populations emphasized by AMOVA results and by very similar F ct values for each sequence variation across the gene, leading to the acceptance of a neutral model of evolution for the analyzed genomic region. Nevertheless, such an absence of sharp TNFRSF13B interpopulation genetic differentiation, in spite of its proved function in humoral responses, is not so unlikely if we take into account the recent remarks about relationships between innate and adaptive components of the immune system 39,40 and the hypothesis of a not negligible involvement of its protein product TACI in innate immune functions. 3 TNFRSF13B, CVID and IgAD from an evolutionary perspective Together with described population-based evolutionary analyses, a direct comparison of Italian samples with CVID and IgAD and control samples was performed applying the same methods.…”
Section: Tnfrsf13b Evolution and Cvid M Sazzini Et Almentioning
confidence: 98%